MEMBANGUN KEKUATAN (POWER) MASYARAKAT AQIDAH DI TENGAH RESTORASI KARAKTER BANGSA - Syukri Syukri (UIN Sumatera Utara Medan, 2017)
To build a people’s power of aqidah in the mid of nation character restoration is quite urgent, bicause without streng aqidah (faith), so there is no spirit in running worshipping activities. Without proper worship, we cennot build good nation. This can cradicate negative straims provided by modern technology and globalization. There fore a serious attempt should be conducted by all of us to build a people’s power of aqidah faith for nation character restoration.